2-N-Benzyl-2,6-dide-oxy-2,6-imino-3,4-O-iso-propyl-idene-d-allono-nitrile. - Ayers, B; Jenkinson, S; Fleet, G; Thompson, A (2013)
X-ray crystallography firmly established the relative stereochemistry of the title compound, C16H20N2O3. The acetonide ring adopts an envelope conformation with one of the O atoms as the flap and the piperidine ring adopts a slightly twisted boat conformation. The absolute configuration was determined by use of d-ribose as the starting material. The compound exists as O-H⋯O hydrogen-bonded chains of mol-ecules running parallel to the b axis.